IMPLEMENTATION OF DEMOCRATIC LEADERSHIP STYLE IN THE PHARMACY INSTALLATION AT LATEMMAMALA HOSPITAL, SOPPENG - Andi Jenni Indriakati; Nur Achriaty Achmar; Rudy; Puji Rahmah (Journal of Golden Generation Abdimas, 2026)
This study aims to introduce and implement a visionary leadership style in the Pharmacy Installation of RSUD Soppeng as an effort to improve staff performance and rebuild staff trust. Visionary leadership emphasizes long-term vision, innovation, and the leader’s ability to inspire and motivate staff to work toward shared goals. The target of this activity was the staff of the Pharmacy Installation at RSUD Latemmamala, who experienced a decline in overall trust due to leadership perceived as lacking firmness in directing the team. The methods employed included direct observation through workplace interactions, interviews with the head and staff of the Pharmacy Installation, and direct observation of real working conditions within the hospital environment. The proposed activities consisted of obtaining permission to conduct the program, organizing workshops or socialization sessions on the application of visionary leadership to support improvements in pharmaceutical service quality, documenting all stages of the activity, and preparing a comprehensive report containing observations, analysis, constraints, and recommendations for future activities. Overall, the results indicate that visionary leadership is highly effective in a dynamic work environment such as the Pharmacy Installation of RSUD Soppeng. The findings reveal a strong relationship between the implementation of visionary leadership and improvements in staff discipline, responsibility, and professionalism. Thus, the leader’s ability to clearly communicate a shared vision and inspire subordinates is a key factor in building a solid pharmacy team that is adaptive to change and oriented toward improving the quality of patient services at RSUD Soppeng.